1995
DOI: 10.1128/cmr.8.4.515
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcosis in the era of AIDS--100 years after the discovery of Cryptococcus neoformans

Abstract: Although Cryptococcus neoformans and cryptococcosis have existed for several millennia, a century has passed since the discovery of this encapsulated yeast and its devastating disease. With the advent of the AIDS pandemic, cryptococcal meningitis has emerged as a leading cause of infectious morbidity and mortality and a frequently life-threatening opportunistic mycosis among patients with AIDS. Both basic and clinical research have accelerated in the 1990s, and this review attempts to highlight some of these a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
558
0
18

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,060 publications
(586 citation statements)
references
References 485 publications
(628 reference statements)
10
558
0
18
Order By: Relevance
“…(Casadevall and Perfect 1998). The literature on gender differences in C. neoformans infections is complicated as the majority of studies reported that males have an increased risk of C. neoformans infection (Amornkul et al 2003;Dromer et al 1996a, b;Hajjeh et al 1999;Micol et al 2007;Mitchell and Perfect 1995;Sorvillo et al 1997) while several studies, reported an increased risk of C. neoformans infections in females (Chuang et al 2008;Jean et al 2002). A possible explanation for this difference is that most of the patients in these two studies were not infected with human immunodeficiency virus (HIV).…”
Section: Fungal Infectionsmentioning
confidence: 69%
“…(Casadevall and Perfect 1998). The literature on gender differences in C. neoformans infections is complicated as the majority of studies reported that males have an increased risk of C. neoformans infection (Amornkul et al 2003;Dromer et al 1996a, b;Hajjeh et al 1999;Micol et al 2007;Mitchell and Perfect 1995;Sorvillo et al 1997) while several studies, reported an increased risk of C. neoformans infections in females (Chuang et al 2008;Jean et al 2002). A possible explanation for this difference is that most of the patients in these two studies were not infected with human immunodeficiency virus (HIV).…”
Section: Fungal Infectionsmentioning
confidence: 69%
“…Filobasidiella neoformans (Cryptococcus neoformans) is an encapsulated yeast that causes self-limiting, asymptomatic pulmonary infections in immunocompetent hosts [1,2] and symptomatic infections in individuals with depressed cell-mediated immunity, particularly those with human immunodeficiency virus (HIV)-1 infection or lymphoproliferative disorders and those on immunosuppressive therapy due to organ transplantation [3,4]. It is worth noting that a significant decline in the incidence of cryptococcosis has been recently observed in AIDS patients, due to the use of highly active antiretroviral therapy (HAART).…”
Section: Introductionmentioning
confidence: 99%
“…Infolge interkontinentaler Migration und Ferntourismus treten solche "exotische" Systemmykosen vereinzelt auch in Europa auf [13]. Kryptokokkose, frĂŒher als "EuropĂ€ische Blastomykose" fast nur bei Patienten mit Hodgkin-Lymphom beobachtet, ist inzwischen bei HIV-Patienten im AIDS-Stadium die hĂ€ufigste terminale Systemmykose [34]. Die Erreger disseminieren hĂ€matogen unter septischen Krankheitssymptomen und befallen,ausgehend von einer primĂ€ren Lungeninfektion, terminal besonders das ZNS [35].…”
Section: Differenzialdiagnostische Aspekteunclassified